2019
DOI: 10.1108/lodj-04-2019-0160
|View full text |Cite
|
Sign up to set email alerts
|

Ethical leadership, perceived organizational support and citizenship behaviors

Abstract: Purpose Utilizing organizational support theory, the purpose of this paper is to examine the mediation effect of perceived organizational support (POS) on the relationship between ethical leadership and citizenship behavior, and investigate the moderating effect of ethnic dissimilarity in the research model. Design/methodology/approach Using a self-administered questionnaire, data were collected from 294 academics of private universities in China, Malaysia and Thailand. The collected data were analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 77 publications
0
29
0
1
Order By: Relevance
“…Scholars have argued that, in general, ethical leadership can promote followers' prosocial behaviors (e.g. organizational citizenship behavior) (Tan et al, 2019;Yang and Wei, 2018) and prevent their deviant or unethical behaviors (Brown and Mitchell, 2010;Moore et al, 2018;Treviño et al, 2014). In this study, given that leadership links to followers' behaviors, we are interested in investigating whether ethical leadership plays a vital role in determining an employee's unethical pro-organizational behavior (UPB), defined as "actions that are intended to promote the effective functioning of the organization or its members and violate core societal values, mores, laws, or standards of proper conduct" (Umphress and Bingham, 2011, p. 622).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have argued that, in general, ethical leadership can promote followers' prosocial behaviors (e.g. organizational citizenship behavior) (Tan et al, 2019;Yang and Wei, 2018) and prevent their deviant or unethical behaviors (Brown and Mitchell, 2010;Moore et al, 2018;Treviño et al, 2014). In this study, given that leadership links to followers' behaviors, we are interested in investigating whether ethical leadership plays a vital role in determining an employee's unethical pro-organizational behavior (UPB), defined as "actions that are intended to promote the effective functioning of the organization or its members and violate core societal values, mores, laws, or standards of proper conduct" (Umphress and Bingham, 2011, p. 622).…”
Section: Introductionmentioning
confidence: 99%
“…According to recent research, when an ethical leader demonstrates al-truistic behaviors, such behavior is perceived by subordinates as caring and responsible behaviors. Subsequently, subordinates emulate these behaviors and demonstrate OCB [41]. O'Keefe et al [42] found that ethical leadership interacts with coworker ethicality to predict employees' ethical intentions and OCB.…”
Section: Ethical Leadership and Employees' Ocbmentioning
confidence: 99%
“…If supervisors respect their employees' rights and dignity, care about their welfare, or listen to their concerns and ideas, employees will feel happy or optimistic [35,57]. Conversely, if employees believe that the leader exhibits unethical behavior, such as not intervening or correcting unethical behavior, or failing to communicate their expectations of employees' ethical behavior and mutual treatment, they will feel angry, worried, and unhappy [41]. The key characteristics of ethical leadership include honesty, trustworthiness, fairness, conscientiousness, and compassion.…”
Section: Mediation Of Affective Well-being On the Relationship Between Ethical Leadership And Employees' Ocbmentioning
confidence: 99%
“…When employees felt fully supported by the organization, they will foster a sense of debt of gratitude because they feel fully supported by the organization which will impact the performance and behavior of those who want to work beyond their obligations (OCB). Based on the principle of reciprocity, organizational support for employees not only helps colleagues, but also increases their own job satisfaction and organizational commitment, while reducing resignation and absences, thereby stimulating employee performance [12] POS found to be positively related with OCB which reported in several research of [30], [31], [32], [33], [34], [35], [36]. So, from the previous researches, results illustrated that perceived organizational support has a positive and strong effect on organizational citizenship behavior and a positive association with it.…”
Section: The Correlation Between Perceived Organizational Support (Pos) and Ocbmentioning
confidence: 99%